MILITARY RECONSTITUTION: HISTORICAL ORIGINS, ADMINISTRATIVE FEATURES AND FURTHER VECTORS OF IMPROVEMENT IN UKRAINE - FRADYNSKYI, Oleksandr; KONOVALCHUK, Dasha; KARAVAN, Victoria (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines the evolution of the military levy as a type of extraordinary taxation, formed and applied by the state in the event of force majeure. It is concluded that extraordinary taxation originates in the states of the ancient world, and the first documentary mention of its application, called «aesphora», dates back to 428 BC, in the ancient Greek polis of Athens. Extraordinary taxation is not something new for Ukraine, because as a result of the man-made disaster, a levy was introduced to the Fund for the implementation of measures to eliminate the consequences of the Chernobyl disaster and social protection of the population. The military levy in Ukraine was introduced in the summer of 2014, as an additional source of budget revenues, which should have a targeted use. According to the method of collection, it was a surcharge of 1.5 percent to the national mandatory payment- personal income tax and was a consensus tax. The tax is characterized by low fiscal efficiency- its share in the State Budget revenues ranges from 2.24 to 3.51% and covered about 20% of all defense spending (in the period until 2022). An analysis of the features of the functioning of the military levy shows that, despite the temporary nature of its collection, there is an urgent need to "legalize" this payment in the Tax Code of Ukraine, especially taking into account the changes in its payment, which came into force on January 1, 2025. Another aspect of improving its collection is the need for a more equitable distribution of the tax burden under this tax among Ukrainian society and a change in the paradigm of its application from direct taxation of income of the population to indirect taxation, through a price mechanism, which will allow attracting to taxation those incomes that are formed in the sphere of shadow economic activity.